Value Relevance of Corporate Economic Sustainability Reporting of Financial Services Quoted Firms in Nigeria - Alade, Muyiwa Ezekiel; Adepiti, Wilson Adebayo; Igbekoyi, Olusola Esther; Olofintuyi, Ademola Tosin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
The focus of this study is to examine the effect of corporate economic sustainability reporting on value of Nigerian financial services quoted firms. The study employed ex-post facto research design. Secondary data were obtained through annual reports published by the firms covering a period of 2010 to 2020. The population of the study consist 51 listed financial services firms. The sample size comprised of 35 financial services firms listed on Nigerian Exchange Group (NGX) that have consistently submitted their annual reports to the NGX from 2010 to 2020, have adhered to Sustainability Reporting Guideline in line with GRI (G4), have been publicly listed on NGX not later than year 2010 and functional firms that have been incorporated for at least the past 11 years. The analysis was achieved using descriptive and panel corrected standard error (PCSE) regression. The study revealed that market presence, economic performance, and indirect economic impacts, as measures of economic sustainability reporting, present positive and significant effect on value relevance, while procurement practices have insignificant effect. The study concluded that any enhancement on the firms policy direction relating to economic sustainability reporting will result to improved performance of firms in the stock market, suggesting that quoted firms should report their corporate economic sustainability services to improve their value.